Enjoyment or involvement? Affective-motivational mediation during learning from a complex computerized simulation. (November 2017) - Brom, Cyril; Děchtěrenko, Filip; Frollová, Nikola; Stárková, Tereza; Bromová, Edita; D'Mello, Sidney K.
Abstract: There is increased interest in augmenting multimedia instructional materials to elevate learners' positive affective-motivational states in order to improve learning. However, these efforts have only been partly successful and mediational effects of positive affective-motivational states have not always been established. In this study, university students ( N = 65) from the Czech Republic, a country where beer brewing is a source of national pride, were informed that they would either study how to brew beer (high intrinsic motivation condition) or how to prepare a citrate substrate (low intrinsic motivation condition). The 90-min simulation environment used for learning was about beer brewing in both cases, with superficial changes to instructions and graphics to disguise the topic manipulation. Generalized positive affect, overall enjoyment, flow, and learning involvement were higher in the beer brewing condition (Cohen's d = 0.44–0.87) as were learning gains when measured immediately (retention: d = 0.48; transfer: d = 0.46) and a month later (retention: d = 0.66; transfer: d = 0.62). However, only learning involvement and flow positively mediated the influence of the topic manipulation on immediate learning outcomes; there were no mediation effects on delayed learning outcomes after co-varying out immediate learning. The findings corroborate results from extant studies on the importance of topic interest in learning from instructional texts. They also indicate that affective-motivational mediation is one, but not the only, mechanism by which topic-based intrinsic motivation manipulations influence learning and that induced positive affective-motivational states can be differentially related or unrelated to learning. Highlights: Learners studied a more vs. less motivating topic using a 90-min simulation. The simulation covered the same content (i.e., beer brewing) in both cases. The motivating topic enhanced enjoyment, learning involvement, and learning gains. Involvement, but not enjoyment, mediated motivation effects on immediate learning. Neither enjoyment nor involvement mediated motivation effects on delayed learning.